2009
DOI: 10.1198/jasa.2009.0113
|View full text |Cite
|
Sign up to set email alerts
|

Testing Dependence Among Serially Correlated Multicategory Variables

Abstract: The contingency table literature on tests for dependence among discrete multicategory variables is extensive. Standard tests assume, however, that draws are independent and only limited results exist on the effect of serial dependency-a problem that is important in areas such as economics, finance, medical trials, and meteorology. This article proposes new tests of independence based on canonical correlations from dynamically augmented reduced rank regressions. The tests allow for an arbitrary number of catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
133
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(133 citation statements)
references
References 35 publications
0
133
0
Order By: Relevance
“…One implication of serial correlation is that the usual sampling variance of the score obtained by assuming independence is no longer valid. This phenomenon has been recognized by Lahiri and Yang (2015) and Pesaran and Timmermann (2009) in various scenarios. Wilks (2010) has shown that the failure to accommodate positive serial correlation will significantly underestimate the standard error of the Brier (skill) score and the magnitude of underestimation depends on the event probability and the quality of the forecast.…”
Section: Introductionmentioning
confidence: 82%
“…One implication of serial correlation is that the usual sampling variance of the score obtained by assuming independence is no longer valid. This phenomenon has been recognized by Lahiri and Yang (2015) and Pesaran and Timmermann (2009) in various scenarios. Wilks (2010) has shown that the failure to accommodate positive serial correlation will significantly underestimate the standard error of the Brier (skill) score and the magnitude of underestimation depends on the event probability and the quality of the forecast.…”
Section: Introductionmentioning
confidence: 82%
“…Tossing a fair coin on a su¢ ciently long sample already predicts the direction of change correctly about 50% of the time, so a model needs to attain a success ratio greater than 0:5 to provide an improvement in directional accuracy over pure chance. 8 The statistical signi…cance of the directional accuracy relative to pure chance (as implied by the directional accuracy of tossing a fair coin) is assessed based on our implementation of the test of Pesaran and Timmermann (2009).…”
Section: Multivariate Bvar (Bvar4-fp Bvar4-mp)mentioning
confidence: 99%
“…Blaskowitz and Herwartz (2011) and Pesaran and Timmermann (2009) have developed tests designed to take care of the serial correlation while testing dependence among binary variables. Wilks (2010) has shown that the failure to accommodate serial correlation will seriously underestimate the standard error of the Brier skill score.…”
Section: Introductionmentioning
confidence: 99%
“…Wilks (2010) has shown that the failure to accommodate serial correlation will seriously underestimate the standard error of the Brier skill score. Pesaran and Timmermann (2009) cite many articles that deal with the effect of serial dependence on the chi-squared tests of independence based on two-way contingency tables. Our paper parallels this literature in that we robustify the current procedures to accommodate serial dependence in the parametric binormal ROC model.…”
Section: Introductionmentioning
confidence: 99%